The Association Between Nutrition, Physical Activity, and Weight Status Among Adults in Georgia - Trang Nguyen; Janani Thapa; Donglan Zhang; Elizabeth Pullekines (Georgia Southern University, 2017)
Background: Obesity is classified as having a body mass index (BMI) greater than 30 and is associated with higher risks of type 2 diabetes, coronary heart diseases, hypertension, and other adverse health outcomes. In 2015, the prevalence of self-reported obesity among adults in Georgia was 30.7. The present study focused on how, in 2015, lifestyle factors, specifically nutrition and physical activity levels, related with weight status in Georgia. Methods: The dataset used for this analysis was from the 2015 Behavioral Risk Factor Surveillance System. The association between weight status (as measured by BMI) and nutrition and physical activity levels was examined by use of linear regressions, controlling for socio-demographic variables. Results: The sample consisted of 3,543 adult respondents in Georgia, of whom 2,285 (64.5%) were overweight or obese. Regarding the variables assessing nutrition, vegetable consumption had a significant association with weight status: one unit increase in consumption of vegetables decreased BMI by 0.009 (p=0.039). Conclusions: Vegetable consumption was negatively associated with BMI. Future research should examine, with more robust measures, the relationship between physical activity levels and weight status and determine how other lifestyle factors relate to weight status. This will become increasingly relevant, as the rates for obesity in Georgia and the United States continue to trend upward. Key words: obesity, lifestyle factors, nutrition, physical activity, weight status, BMI